Economic Impacts of Pre-Salt on a Regional Economy: The Case of Espirito Santo, Brazil - Eduardo Haddad; Ana Carolina Giuberti (European Regional Science Association (ERSA), 2010)
Brazilian government has recently confirmed the discovery of a huge oil and natural gas field in the pre-salt layer off the country's southeastern coast. It has been said that the oil fields can boost Brazil's oil production, and turn the country into one of the largest oil producers in the world. The fields are spatially concentrated in the coast area of a few Brazilian states, that may be directly benefited by oil production. This paper uses an interregional CGE model to assess the impacts of pre-salt on the economy of the State of Espirito Santo, a region already characterized by an economic base heavily reliant on natural resources. We focus our analysis on the structural economic impacts, both in the short run, medium run and long run.
Keywords: 330